Produção de leite, duração da lactação e intervalo de partos em búfalas mestiças Murrah - Bezerra Junior, Jailton da Silva; Fraga, Angelina Bossi; Couto, Alberto de Gusmao; Barros, Camila da Costa [UNESP]; Oliveira Silva, Rafael Medeiros de [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2014)
This study aimed to evaluate the potential for milk production (MP), lactation length (LL) and calving interval (CI), analyze the environmental component affecting these traits, and to estimate the heritability and repeatability for milk production in crossbreds of Murrah buffalo cows in the state of Alagoas, Brazil. Data was composed of 487 observations of MP from 136 lactations recorded between the years of 2000 and 2010. In the analysis of variance for PL, the fixed effects were season (1- October to March, 2 -April to September) and year of the beginning of lactation, calving order and the LL (covariate). For the analysis of LL only the fixed effect of year of the beginning of lactation was included, and finally for the CI analysis, year of the beginning of lactation and calving order. The estimates of covariance were obtained using unicharacteristic analysis by Bayesian inference method, applyingan animal model, through Gibbs sampling. The additive genetic, permanent environment and residual effects were included as random effects in the model. The averages (sd) of MP, LL and CI were 2,218.03 kg (408.18), 282.59 days (39.48) e 422.49 days (91.05), respectively. All the effects included in the models were important (P<0.01). The estimates of heritability and repeatability for PL were 0.29 and 0.69, respectively. The results suggest that there is a moderate genetic variability among individuals for PL, indicating the possibility to obtain gain using selection.
Milk production, lactation length and calving interval in crossbreds of Murrah buffalo cows
Keywords: Buffaloes; Heritability; Repeatability; Reproductive performance